2019
DOI: 10.1002/er.4527
|View full text |Cite
|
Sign up to set email alerts
|

Poly‐3‐hexylthiophene doped with iron disulfide nanoparticles for hybrid solar cells

Abstract: Summary In this work, the pyrite crystalline phase of iron disulfide nanoparticles (FeS2) about 20 to 30 nm was obtained by a two‐pot thermal method at 220°C. Subsequently, different concentrations of these nanoparticles were used as a doping agent for the conjugated poly‐3‐hexylthiophene (P3HT). The electrical resistivity of P3HT was decreased almost three orders of magnitude while adding FeS2 nanoparticles as doping, and dichlorobenzene solvent was a determinant factor for the dispersion of polymer with nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…All the films showed P3HT:PC 61 BM peaks in the range between 334 and 600 nm, revealing that the CdS NCs are blended adequately with polymers. It is observed that the absorption peak intensity increases with respect to the concentration of NCs, indicating a strong interaction between the P3HT:PC 61 BM polymers and CdS NCs 48 . However, absorption peak intensity was slightly reduced for 1 wt% of CdS NCs.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…All the films showed P3HT:PC 61 BM peaks in the range between 334 and 600 nm, revealing that the CdS NCs are blended adequately with polymers. It is observed that the absorption peak intensity increases with respect to the concentration of NCs, indicating a strong interaction between the P3HT:PC 61 BM polymers and CdS NCs 48 . However, absorption peak intensity was slightly reduced for 1 wt% of CdS NCs.…”
Section: Resultsmentioning
confidence: 92%
“…It is observed that the absorption peak intensity increases with respect to the concentration of NCs, indicating a strong interaction between the P3HT:PC 61 BM polymers and CdS NCs. 48 However, absorption peak intensity was slightly reduced for 1 wt% of CdS NCs. Hence, it is apparent that the highest absorption intensity of P3HT:PC 61 BM was obtained at 0.5 wt% concentration of CdS NCs.…”
Section: Resultsmentioning
confidence: 96%
“…In addition to above-mentioned NBG QDs delivering considerable photovoltaic performance, there are some binary QDs that currently offer petty results with modest PCEs but have development potential, such as SnS, [59,[168][169][170][171] FeS 2 , [60,[172][173][174] Bi 2 S 3 , [175] HgTe, [62,176,177] InAs, [63] InP, [178,179] etc. Table 6 summarizes the recent reports of photovoltaic performance for these potential binary QD-based QDSCs.…”
Section: Other Potential Binary Quantum Dotsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Evolution of nonfullerene acceptor particularly plays a vital role for achieving highperformance OPVs. [1][2][3][4][5][6][7][8] Evolution of nonfullerene acceptor particularly plays a vital role for achieving highperformance OPVs.…”
Section: Introductionmentioning
confidence: 99%
“…Organic photovoltaic cells (OPVs) with bulkheterojunction structure have achieved significant progress, benefiting from the continuous material development and device optimization. [1][2][3][4][5][6][7][8] Evolution of nonfullerene acceptor particularly plays a vital role for achieving highperformance OPVs. Compared with traditional fullerene acceptors such as PC 61 BM or PC 71 BM, nonfullerene acceptors exhibit excellent optical absorption properties, easily tunable molecular energy levels, and potential for processing OPVs with low voltage loss.…”
Section: Introductionmentioning
confidence: 99%